Utilization of Information Resources andn Services and its Imapct on the Research Output of Faculty at the University of Sindh Jamshoro,Pakistan - Muhammad Ismail, Sana Gul (IJoLIS, 2024)
Purpose: The study examines the utilization of information resources and services and its impact on the research output of faculty members of Sindh University Jamshoro.